Strategies to Reduce Stunting Rates Through Increased Awareness and Collective Action in the Community of Setanggor Village East Lombok Regency - Bunga Suryani; Yani Satriawati; Riskia Dwi Lestari; Husnul Hotimah; Pinka Izmy Apriani; Ayu Mina Apriani; Wahyu Hidayatullah; Moh. Irwan; Lalu Gilang Ramadan Alfarido; Adrian Maulana; Agus Suroso (Unram Journal of Community Service, 2024)
Setanggor is one of the villages located in the Sukamulia District, East Lombok Regency, West Nusa Tenggara Province. The community in this village, 80% of whom work as farmers, spends a lot of time in the fields. However, the prevalence of stunting in this village is still relatively high. Therefore, the goal of the Community Service Program (KKN) by the Mataram University's PMD (Community Development Program) during the period of December 2023 to February 2024 is to assist the community in addressing stunting through increasing awareness and collective action in stunting prevention. The methods used include socialization, distribution of nutritious food, and Posyandu (Integrated Health Service Post). The results obtained from these activities include increased awareness and knowledge among the villagers regarding the importance of maintaining a healthy and clean lifestyle, as well as the need for adequate intake of nutritious food to prevent malnutritionÂ inÂ children